The Keefektifan Model Pembelajaran Cooperative Integrated, Reading and Composition (CIRC) dalam Pembelajaran Keterampilan Menulis Puisi Siswa Kelas VIII SMP Al Ikhlas Jatinegara Tahun Pelajaran 2019/2020 - Zidni Ilma Nafi'ah; Vita Ika Sari; Burhan Eko Purwanto (Cakrawala: Jurnal Pendidikan, 2020)
The purpose of this study was to determine the effectiveness of the CIRC learning model in teaching poetry writingskills for VIII grade students of SMP Al Ikhlas Jatinegara in the 2019/2020 academic year. The research approachused is a descriptive quantitative approach to the type of experimental research. There are two types of variables inthis study, namely the independent variable and the dependent variable. The independent variable is the CIRC learningmodel, and the dependent variable is the students' poetry writing skills. The population of this study were students ofclass VIII SMP Al Ikhlas Jatinegara with a total of 50 students. The sampling technique used is a non-probabilitysampling technique with a census sampling type. The data collection technique used was a test technique with researchinstruments in the form of pretest and postest questions, as well as the criteria for assessing the ability to write poetry.The data analysis technique used is the t-test of SPSS 16.0 application and manual calculation of the formula as a dataanalysis technique. The results of this study were that the CIRC learning model was effectively used in learning poetrywriting skills for eighth grade students of SMP Al Ikhlas Jatinegara in the 2019/2020 academic year. The effectivenessof the CIRC learning model can be shown from the results of data analysis with the SPSS 16.0 application, which is asignificance value of 2 tailed 0.000 less than the significant level of 0.05. In addition, the manual formula calculationshows that tcount = 10.30 while t table = 1.67 with a significance level of 0.05 and degrees of freedom 48. Thus thenull hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.